Pinghe bibliotheater. Open Architecture - Filosa, Francesca (Platform, 2021)
An immense blue body, triangular in shape with rounded corners, wound by a large glass mouth serving as an entrance and a vent at the top as a skylight. This is what the Pinghe Bibliotheater - nicknamed The Blue Whale - looks like, the latest project by OPEN Architecture. The big blue whale is located in Shanghai, China.